2015
DOI: 10.1134/s0006297915030074
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid structures of polycationic aluminum phthalocyanines and quantum dots

Abstract: Semiconductor nanocrystals (CdSe/ZnS quantum dots, QDs) were used as inorganic focusing antenna, allowing for the enhancement of fluorescence and photosensitizing activity of polycationic aluminum phthalocyanines (PCs). It was found that QDs form stable complexes with PCs in aqueous solutions due to electrostatic interactions. In such hybrid complexes, we observed highly efficient nonradiative energy transfer from QD to PC, leading to a sharp increase in the effective absorption cross section of PC in the abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Although many researchers have prepared conjugates between quantum dots and various different PSs to carry out PDT [101103], a recent study showed that graphene quantum dots could mediate PDT on their own without any added PS [87]. …”
Section: Nanotechnologymentioning
confidence: 99%
“…Although many researchers have prepared conjugates between quantum dots and various different PSs to carry out PDT [101103], a recent study showed that graphene quantum dots could mediate PDT on their own without any added PS [87]. …”
Section: Nanotechnologymentioning
confidence: 99%
“…The ability of COCP to quench 1 O 2 was tested by illumination of common 1 O 2 sensitizers, either tetra-and pentakis(cholinile) aluminium phthalocyanines (AlPCs) (31) or Rose Bengal (as used in previous 1 O 2 quenching assays (5, 10)), using Singlet Oxygen Sensor Green (SOSG) fluorescence to monitor 1 O 2 generation. Both, COCP and OCP caused a profound reduction of O 2 yield (Supplementary Figure S6).…”
Section: Functional Properties Of Cocpmentioning
confidence: 99%
“…In this case, the PS-NP conjugate must be created on the basis of non-covalent interactions [5,6]. Second, the NP can be given additional functionality; for example, it can be used as a lightharvesting antenna that enhances the absorption capacity of the PS in the visible [7,8] or IR region [9,10] of the spectrum. Thus, the PS will mediate photodynamic reactions when combined with NPs and, therefore, the PS-NP complex should be stable.…”
Section: Introductionmentioning
confidence: 99%